Determinants of Zakat, Infaq, and Sadaqah Collection: Study in BAZNAS West Java - Naila Firdausi; Cupian Cupian (International Journal of Zakat, 2026)
PurposeThis study examines the determinants of zakat, infaq, and sadaqah (ZIS) collection at BAZNAS West Java Province by analysing internal operational factors and external macroeconomic conditions. Design/Methodology/ApproachA quantitative time series approach is employed using quarterly data from Q1 2017 to Q3 2024. The Autoregressive Distributed Lag (ARDL) model is applied to estimate short-term and long-term relationships between ZIS collection and human resource expenses, zakat socialization expenses, exchange rate, and Gross Regional Domestic Product (GRDP). FindingsThe results reveal that in the short term, human resource expenses, exchange rate, and GRDP have a positive and significant effect on ZIS collection, while zakat socialization expenses are insignificant. In the long term, none of the variables show a statistically significant effect on ZIS collection. Research limitations/implicationsThe study is limited to a single provincial zakat institution with a relatively small number of observations. Future research may expand institutional coverage and incorporate governance, transparency, and behavioural variables. Practical implicationsZakat institutions should prioritize strengthening human resources and partnership-based fundraising strategies to enhance short-term collection performance. Social implicationsImproved ZIS collection supports the role of zakat institutions in poverty alleviation and social welfare. Originality/valueThis study contributes by providing dynamic empirical evidence on ZIS collection determinants at the provincial level using the ARDL approach.